Kidney transplantation in patients with previous renal cancer: a critical appraisal of current evidence and guidelines - Frascà, Giovanni M.; Brigante, Fabiana; Volpe, Alessandro; Cosmai, Laura; Gallieni, Maurizio; Porta, Camillo (Journal of nephrology, 2019)
Due to the increasing occurrence of renal cell carcinoma (RCC) in the general population and the high prevalence of chronic kidney disease among cancer patients, many people with a previous RCC may eventually require renal replacement therapy including kidney transplantation. They should accordingly be evaluated to assess their life expectancy and the risk that the chronic immunosuppressive therapy needed after grafting might impair their long-term outcome. Current guidelines on listing patients for renal transplantation suggest that no delay is required for subjects with small or incidentally discovered RCC, while the recommendations for patients who have been treated for a symptomatic RCC or for those with large or invasive tumours are conflicting. The controversial results reported by even recent studies focusing on the cancer risk in kidney graft recipients with a prior history of malignancy do not help to clarify the doubts arising in everyday clinical practice. Several tools, including integrated scoring systems, are currently available to assess the prognosis of patients with a previous RCC and, although they have not been validated in subjects receiving long-term immunosuppressive drugs, they can be used to identify patients suitable to be listed for grafting. Among these, the Leibovich score is currently the most widely used as it has proved simple and reliable enough and helps categorize renal transplant candidates. According to this system, subjects with a score from 0 to 2 are at low risk and may be listed without delay, while those with a score of 6 or higher should be excluded from grafting. In addition, other factors have an established positive prognostic value, including chromophobe or clear cell papillary tumour, or G1 grade cancer; on the contrary, medullary or Bellini’s duct carcinoma or those with sarcomatoid dedifferentiation at histological examination should be excluded. All other patients would be better submitted to careful individual evaluation by an Oncologist before being listed for renal transplantation, pending studies specifically focusing on cancer risk evaluation in people already treated for malignancy receiving long-term immunosuppressive therapy.